Community Governance in Cultural Tourism: The Role of Social Capital in Sustaining Community-Based Tourism in Indonesia - Susi Hardjati; Binti Azizatun Nafi’ah (Dealings Foundation Institute, 2026)
Community-based tourism has recently been introduced as a new concept for developing tourism sites with the local community playing a significant role in the management of tourism sites. Despite the potential of community-based tourism, there are a number of challenges facing the sustainability of community-based tourism sites, such as low participation rates, lack of coordination among tourism stakeholders, and inefficient utilization of social potential in the community. The purpose of the current study was to investigate the impact of social capital on community governance and tourism sustainability in the Bandar Kidul Ikat Weaving Tourism Village in Kediri City. This research was conducted using a quantitative approach with a survey method of 152 respondents from the community and business actors who are active in tourism activities in the Bandar Kidul Ikat Weaving Village. Data collection was carried out using a questionnaire method with a Likert scale and analysis using a Structural Equation Modeling method. The results showed that social capital has a positive effect on community governance. In addition, community governance has a positive effect on tourism sustainability. Social capital also has a direct effect on tourism sustainability. This research also demonstrates that social capital has a crucial role in building community governance and tourism sustainability in developing culture-based tourism in the Bandar Kidul Ikat Weaving Tourism Village in Kediri City, Indonesia.